All-atomic and coarse-grained molecular dynamics investigation of deformation in semi-crystalline lamellar polyethylene. (26th September 2018) - Olsson, Pär A.T.; in 't Veld, Pieter J.; Andreasson, Eskil; Bergvall, Erik; Persson Jutemar, Elin; Petersson, Viktor; Rutledge, Gregory C.; Kroon, Martin
Abstract: In the present work we have performed classical molecular dynamics modelling to investigate the effects of different types of force-fields on the stress-strain and yielding behaviours in semi-crystalline lamellar stacked linear polyethylene. To this end, specifically the all-atomic optimized potential for liquid simulations (OPLS-AA) and the coarse-grained united-atom (UA) force-fields are used to simulate the yielding and tensile behaviour for the lamellar separation mode. Despite that the considered samples and their topologies are identical for both approaches, the results show that they predict widely different stress-strain and yielding behaviours. For all UA simulations we obtain oscillating stress-strain curves accompanied by repetitive chain transport to the amorphous region, along with substantial chain slip and crystal reorientation. For the OPLS-AA modelling primarily cavitation formation is observed, with small amounts of chain slip to reorient the crystal such that the chains align in the tensile direction. This force-field dependence is rooted in the lack of explicit H-H and C-H repulsion in the UA approach, which gives rise to underestimated ideal critical resolved shear stress. The computed critical resolved shear stress for the OPLS-AA approach is in good agreement with density functional theory calculations and the yielding mechanisms resemble those of the lamellar separation mode. The disparate energy and shear stress barriers for chain slip of the different models can be interpreted as differently predicted intrinsic activation rates for the mechanism, which ultimately are responsible for the observed diverse responses of the two modelling approaches. Graphical abstract: Image 1 Highlights: All-atomic and coarse-grained atomistic modelling of lamellar separation in semi-crystalline polyethylene was performed. A comparison of the yielding and stress-strain behaviours of explicit and united-atom modelling approaches was made. The two approaches were found to predict to very different yielding and stress-strain behaviours. The disparate response is explained by the widely different critical resolved shear stresses for chain slip of the models.